(untitled) (American International Journal of Sciences and Engineering Research, 2019)
In our past work , some coupling azo- compounds were formatted characterized , chemical identification , which appeared good evidences for production our azo-coupling compounds , while in this paper , these azo-coupling derivatives were studied against types of fungi.